Bernard Lonergan and Alberto Guerreiro Ramos: Dialogues between the existential subject and the parenthetical man - Santos, Laís Silveira; Serafim, Mauricio C.; Pinheiro, Daniel Moraes (Organizações & Sociedade, 2019)
Bernard Lonergan has addressed, among other topics, the issue of human and ethical action, considering the possibility of a path of authenticity and moral achievement that occurs in a specific type of subject, whom he has called the existential subject. Based on this concept, we considered the possibility of a dialogue with Alberto Guerreiro Ramos, who has created the concept of parenthetical man, defined as a being that is rational for excellence, in his substantive dimension. The conception of this model of man goes in an opposite direction of the management theories based on the instrumental rationality. Although Lonergan has not created, explicitly, a substantive theory, his concept of ethics and human highlights aspects that relates to the substantive rationale. Thus, this theoretical essay aims to identify the possible approach between the parenthetical man and the existential subject, based on human action and ethics. We identified that the authors have a similar comprehension of the world and of the human relations, especially regarding the critical consciousness of the parenthetical man and the responsible consciousness of the existential subject.